A low-jitter and low-reference-spur 320 GHz signal source with an 80 GHz integer-N phase-locked loop using a quadrature XOR technique - Liang, Yuan (2022)
This article reports a 320-GHz low-jitter and low-reference-spur signal source consisting of an 80-GHz integer-N phase-locked loop (PLL) and a 320-GHz frequency quadrupler. The 80-GHz PLL features a novel dual-path quadrature exclusive-OR (QXOR) technique to cancel the spurs at the reference frequency and its harmonics, enabling low-spur and low-noise phase locking. The proposed phase detector (PD) also enables frequency detection and lock detection (LD), rendering the band-searching to be decoupled from the loop components. Implemented in a 0.13-μm SiGe BiCMOS technology, the proposed signal source shows a -73.1-dBc reference spur, -113.7-dB/Hz phase noise at 1-MHz offset at 40.96 GHz, and -90.3-dB/Hz phase noise at 1-MHz offset at 311.8 GHz. It achieves an integrated jitter of 66.9 fs <tex>$_{{rms}}$</tex> at 40.96 GHz and 122 fs <tex>$_{{rms}}$</tex> (both integrated from 10 kHz to 100 MHz) beyond 300 GHz, with a total division ratio of 512. The LD time is at the microsecond level. The maximum output power is -3.24 dBm, and the power consumption is 372 mW.